STRATEGY IN OPTIMIZING INCOME FROM PUBLIC ROAD SIDE PARKING LEVIES IN SURABAYA CITY - Yoga Raffi Krisnanda Putra; Agus Widiyarta (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
This research aims to determine, analyze, dan describe the strategy taken by the Surabaya City Transportation Agency in optimizing public roadside parking levy revenue. Regional Original Revenuee (ROR) is vital for the Regional Government in implementing regional autonomy and setting a budget to carry out development programs in the region. One source of ROR comes from regional levies. One type of regional levy is a levy on public roadside parking services. The city of Surabaya as the capital city of East Java Province as well as the center of the economy in East Java Province is expected to receive public roadside parking levies that reach the target, one of the factors that is considered is because the total number of residents and motorized vehicles is increasing every year. The Technical Implementtation Unit (TIU) for Public Roadside Parking is a TIU under the Transportation Agency which is tasked with managing public roadside parking levies. The research method used are observation, interviews, and documentation. This study uses Fred R. David strategic management theory which consists of Strategy Formulation, Strategy Implementation, and Strategy Evaluation. The results of this study indicate that the strategic management of the Transportation Agency in optimizing revenue from public roadside parking fees was less than succesfull.